CD8 T cells primed in the gut‐associated lymphoid tissue induce immune‐mediated cholangitis in mice. Issue 2 (18th December 2013) - Seidel, Daniel; Eickmeier, Ira; Kühl, Anja A.; Hamann, Alf; Loddenkemper, Christoph; Schott, Eckart
<x xml:space="preserve">Abstract</x> The pathogenesis of primary sclerosing cholangitis (PSC) remains poorly understood. Since PSC predominantly occurs in patients with inflammatory bowel disease, autoimmunity triggered by activated T cells migrating from the gut to the liver is a possible mechanism. We hypothesized that T cells primed in the gut‐associated lymphoid tissue (GALT) by a specific antigen migrate to the liver and cause cholangitis when they recognize the same antigen on cholangiocytes. We induced ovalbumin‐dependent colitis in mice that express ovalbumin in biliary epithelia (ASBT‐OVA mice) and crossed ASBT‐OVA mice with mice that express ovalbumin in enterocytes (iFABP‐OVA mice). We analyzed T‐cell activation in the GALT and crossreactivity to the same antigen in the liver as well as the effects of colitis per se on antigen‐presentation and T‐cell activation in the liver. Intrarectal application of ovalbumin followed by transfer of CD8 OT‐I T cells led to antigen‐dependent colitis. CD8 T cells primed in the GALT acquired effector function and the capability to migrate to the liver, where they caused cholangitis in a strictly antigen‐dependent manner. Likewise, cholangitis developed in mice expressing ovalbumin simultaneously in biliary epithelia and enterocytes after transfer of OT‐I T cells. Dextran sodium sulfate colitis led to increased levels of inflammatory cytokines in the portal venous blood, induced activation of resident liver dendritic cells, and promoted the induction of T‐cell‐dependent cholangitis. Conclusion: Our data strengthen the notion that immune‐mediated cholangitis is caused by T cells primed in the GALT and provide the first link between colitis and cholangitis in an antigen‐dependent mouse model. (Hepatology 2014;59:601–611)